Unidades léxicas pluriverbales y rodeo expresivo en los noticiarios de la televisión puertorriqueña - Montalvo Montalvo, Marilyn (2006)
The essay is the product of a research done with a sample of Puerto Rican television news, as part of the project entitled Difusián Internacional del Español, por Radio, Televisián y Prensa: Unidad y Diversidad de la Lengua Española (DIES-RTP). The frequency and the nature of the idiomatic phrases found in the sample are analyzed in order to establish the relationship between the roundabout expressions that many authors perceive in the language of media and the excessive use of these constructions.